Behavioral Biases, Financial Literacy, and Investment Decisions: A Study on Women Entrepreneurs - Heru Baskoro; Alviana Ajeng Hardinto; Dwi Kartika wahyuningsih; Arif Rahman Kuswara (Journal of Advanced Research in Social Sciences and Humanities, 2024)
Aim: The purpose of this study is to analyze the effect of the four heuristic biases Anchoring, Overconfidence, Representativeness as well as availability on the investment choices of female SMEs entrepreneurs in Banyumas, Cilacap and Purbalingga, and to analyze the moderating influence of financial literacy on these relationships. Methodology: Conducted with a sample size of 64 respondents, using quantitative methodology with a structured questionnaire survey and analyzing the data using Smart PLS. Findings: The results prove that there is a strong relationship between financial literacy and investing decision-making, especially in terms of Anchoring and Overconfidence bias. However, financial literacy does not affect the relationship between the four heuristic biases and investing decisions. Overconfidence is proven to have a considerable effect on investment decisions. Implications/Novel Contribution: The research underscores the need to strengthen financial literacy among women entrepreneurs so that they do not fall into the traps of biased investment decisions, while also suggesting further exploration into the scope of financial literacy’s role in overcoming other heuristic biases.